2007
DOI: 10.1073/pnas.0702102104
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vpr usurps Cul4–DDB1[VprBP] E3 ubiquitin ligase to modulate cell cycle

Abstract: The replication of viruses depends on the cell cycle status of the infected cells. Viruses have evolved functions that alleviate restrictions imposed on their replication by the host. Vpr, an accessory factor of primate lentiviruses, arrests cells at the DNA damage checkpoint in G 2 phase of the cell cycle, but the mechanism underlying this effect has remained elusive. Here we report that Vpr proteins of both the human (HIV-1) and the distantly related simian (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
238
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(253 citation statements)
references
References 52 publications
13
238
2
Order By: Relevance
“…4A). Interestingly, in contrast with a recent report showing that the expression level of p53 is relatively high in VprBP-depleted cells (11), our data demonstrated no detectable alteration in the p53 protein level after VprBP knockdown. In checking the transcription of p53-responsive genes, such as p21, Gadd45, Bax, Casp8, and Noxa, by qRT-PCR, we found that RNAi depletion of p53 led to a severe reduction in transcription after DNA damage, indicating that p53 is the major regulator of these genes (Fig.…”
Section: Vprbpcontrasting
confidence: 55%
See 2 more Smart Citations
“…4A). Interestingly, in contrast with a recent report showing that the expression level of p53 is relatively high in VprBP-depleted cells (11), our data demonstrated no detectable alteration in the p53 protein level after VprBP knockdown. In checking the transcription of p53-responsive genes, such as p21, Gadd45, Bax, Casp8, and Noxa, by qRT-PCR, we found that RNAi depletion of p53 led to a severe reduction in transcription after DNA damage, indicating that p53 is the major regulator of these genes (Fig.…”
Section: Vprbpcontrasting
confidence: 55%
“…Given this reversible nature of histone acetylation, cells need to employ additional factors that can recognize and lock in a distinct (de)acetylation status of promoter nucleosomes. In relation to the present study, the cellular depletion of VprBP leads to the increased expression of the p53 target gene p21 (11). These results raise questions about whether VprBP is able to downregulate p53-mediated transcription and, if so, how this would affect cellular responses to DNA damage.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…One of these WD40 domain-containing proteins, VprBP/ DCAF1, contains four WD40 domains and a LisH domain. VprBP was originally identified due to its interaction with the Vpr protein from the human immunodeficiency virus, however, the physiological function and substrates of VprBP/DCAF1 are still unknown (Zhang et al, 2001;Belzile et al, 2007;Hrecka et al, 2007;Le Rouzic et al, 2007;Tan et al, 2007;Wen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…First, the best renowned activity of Vpr, its ability to mediate a G2 arrest of the cell cycle, depends on the activation of the ATR-mediated (ATR: ataxia telangiectasia mutated and Rad3 related) DNA damage response (22). G2 arrest requires Vpr binding to DCAF1, an adaptor of the Cul4A-DDB1 ubiquitin ligase, which is involved in DNA repair in noninfected cells (23)(24)(25)(26)(27)(28)(29). More recently, Vpr has been shown to activate the SLX4 complex (SLX4com) with the help of DCAF1 (21,30).…”
mentioning
confidence: 99%